The internal anticipation of sensory action effects: when action induces FFA and PPA activity - Kühn, Simone; Seurinck, Ruth; Fias, Wim; Waszak, Florian (Frontiers in Human Neuroscience, 2010)
Voluntary action – in particular the ability to produce desired effects in the environment – is fundamental to human existence. According to ideomotor theory we can achieve goals in the environment by means of anticipating their outcomes. We aimed at providing neurophysiological evidence for the assumption that performing actions calls for the activation of brain areas associated with the sensory effects usually evoked by the actions. We conducted an fMRI study in which right and left button presses lead to the presentation of face and house pictures. We compared a baseline phase with the same phase after participants experienced the association between button presses and pictures. We found an increase in the parahippocampal place area (PPA) for the response that has been associated with house pictures and fusiform face area (FFA) for the response that has been coupled with face pictures. This observation constitutes support for ideomotor theory.